Synthesis and characterization of 2-mercaptoethanol-capped manganese-doped zinc sulfide quantum dots-embedded molecularly-imprinted membranes. (2nd January 2022) - Thor, Hui Ying; Teow, Yeit Haan; Ho, Kah Chun
Abstract: The objective of this study is to synthesize QD-embedded molecularly imprinted membranes (MIMs) with 2-mercaptoethanol-capped manganese-doped zinc sulfide quantum dots (ME-capped Mn-doped ZnS QDs) through chemical precipitation followed by surface molecular imprinting. For the synthesis of the MIMs, the weight of ME-capped Mn-doped ZnS QDs was first manipulated, followed by their characterization through transmission electron microscopy (TEM), zeta potential, hydrodynamic particle size, particle size distribution, and Fourier-transform infrared spectroscopy (FTIR). The resultant MIM was characterized by fluorescence intensity and showed an emission peak of 600 nm with an excitation wavelength of 300 nm. Besides, increments in QDs were found to elevate the fluorescence intensity of the MIM, contributing to an improved fluorescence quantum yield. This article indicates that molecularly-imprinted QD-based sensors offer promising biomedical potential in diagnoses and treatment.